Martinus Antonie van Andel (1878–1941) en de volksgeneeskunde: ‘Lost in Translation’? - Snelders, Stephen (Studium, 2013)
Martinus Antonie van Andel (1878–1941) en de volksgeneeskunde: ‘Lost in Translation’?